Customer Value in Improving Indihome Customer's Trust in West Java - Erika Nurmartiani (Global Writing Academica Researching & Publishing, 2022)
The problem facing by IndiHome since this product launched in West Java, is from January 2018 until December 2019 can not reach sales target. There is a decrease in the number of subscribers from 2018 to 2019. Such conditions indicate a decrease in the level of customer trust towards IndiHome products that are allegedly relate to customer value. So, this study aims to examine the influence of customer value on indiHome customer trust in West Java. The research is conducted by using quantitative method. The population is all indiHome customers in West Java. This research is dominated by Quantitative Research, namely a research design that approaches empirical studies to collect, analyze, and display data in numerical form and try to accurately measure something (Cooper & Schindler, 2006). The unit of analysis and observation in this research is IndiHome customer in Bandung City. The observation is conducted in a cross section/one shoot time horizon, meaning that information or data collected directly empirically at one time that is at the end of year 2019. So based on the above description then the population is IndiHome customer in Bandung city, and sample size was taken randomly as many as 50 customers taken in a number of INDIHOME service plaza spread in Bandung. The hypothesis is tested by using Partial Least Square (PLS). The result shows that customer value significantly affect on the increasing customer trust. So the results of this study provide implications to the management of PT Telkom as a reference in an effort to increase customer trust through the efforts to increase customer value.